DEVELOPMENT OF INTERACTIVE MULTIMEDIA FUN EXPLANATION TO IMPROVE SIXTH-GRADE STUDENTS' READING COMPREHENSION OF EXPLANATORY TEXTS - Aulia Rahmawati; Andarini Permata Cahyaningtyas (Universitas Majalengka, 2026)
Elementary school students' ability to read and understand explanatory texts still needs to be improved, while the use of learning media that supports the process of understanding texts interactively is still limited. This study aims to develop a feasible and effective interactive multimedia Fun Explanation to improve the ability to read and understand explanatory texts of sixth-grade elementary school students. This study uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 28 sixth-grade students of SD Negeri Wates 01 Semarang. The feasibility of the product was assessed by material experts, media experts, and educational practitioners, while the effectiveness of the product was tested through a one-group pretest-posttest design. Data collection techniques used interviews, observations, questionnaires, and tests. Data were analyzed descriptively and quantitatively, using the Wilcoxon test and N-Gain. The results showed that the interactive multimedia Fun Explanation obtained an average validation score of 94.1% with a very feasible category. The results of the Wilcoxon test showed a significant difference between the pretest and posttest scores (Z = -4.549; p < 0.05). Furthermore, the N-Gain value of 0.6417 indicates that the developed multimedia is quite effective in improving students' reading comprehension skills. Students' responses to the use of multimedia reached 86%, categorized as very good. Thus, the interactive multimedia Fun Explanation is considered very feasible and quite effective for use in teaching reading comprehension of explanatory texts in elementary schools.